Cycloconverter-type high frequency link inverter for photovoltaic application - Zainal, Salam, Prof. Dr.; Nge, Chee Lim; Toh, Leong Soon; Mohd. Zulkifli, Ramli (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/